Linked Heritage: achievements and next steps - Fresa, Antonella (Archeomatica, 2013)
Linked Heritage: achievements and next steps Linked Heritage is a Best Practice Network which includes ministries, responsible government agencies, content providers and aggregators, leading research centres, publishers and SMEs from 20 EU countries, together with Israel and Russia. The activities are delivered through the work of 7 Work Packages, led by different partners, with the support of 4 European Thematic Working Groups as well as a number of Interdisciplinary National Working Groups. Linked Heritage è una rete di buone pratiche che comprende ministeri, responsabili di agenzie governative, fornitori di contenuti e aggregatori, importanti centri ricerca, editori e PMI provenienti da 20 paesi dell'Unione europea, insieme con Israele e Russia. Il suo scopo principale è da un lato la fornitura di grandi quantità di nuovi contenuti a Europeana, del settore pubblico e privato, e dall'altro il miglioramento della qualità dei contenuti esistenti di Europeana, in termini di ricchezza di metadati, il suo potenziale riutilizzo e la sua unicità .